Response to Lolli: context-specific variability in elite sport - Asimakidis, N. D.; Beato, M.; Bishop, C.; Turner, A. N. (International Journal of Sports Physiology and Performance, 2026)
We appreciate Lolli`s1 interest in our work, yet his comments are grounded in a conceptual framework misaligned with the aims and applied context of our work. By convention, inferential thresholds are often applied directly to practice. Nevertheless, inferential statistics quantify long-run probability by determining what would constitute a "real" change across repeated samples from an assumed population,2 not for the athletes being assessed. Because samples can vary substantially, the magnitude of change required to exceed inferential thresholds (eg, ±1.96 × SD) becomes disproportionately large and, in well-trained athletes whose expected performance adaptations are relatively small, may be practically unattainable.